Human Resource Management Philosophy for Promoting Organisational Performance - Salome Kekelidze (Researchparks Publishing, 2022)
In this thesis human resources management in private sector should be discussed. In particular, the essence and importance, it’s international operation, management obligations, planning of human resources and management strategy should be considered. Furthermore, labor relations, their regulation and nature in Georgia as well as abroad will be fundamentally examined. The main essence of the topic - is human resources, which reflects the wealth of any society and for the development it is possible to produce, improve and utilize the same resources, taking into consideration the interests of each individual. Human views are based on his knowledge, qualifications and experience. This also refers to the management of human resources. Any decision regarding the personnel, which is taken by the management, is derived from the individual perception of human resources management. As the experience has shown, in terms of global competition the success is achieved by the managers, who can better adjust to variable conditions. This, in turn, requires the existence of the loyal and qualified employees as well. The human resource manager's profession is significantly different from traditional staff work. It is related to the integration and successful implementation of the organization's goals. The important stage of this process is assimilation of the idea of system approach, not only functional but also an organization as a system and Human Resource Management was formed based on new different models. People represent important resources of the organization, they determine the future strategy of the company, and the strategy itself is realized by people. The success of the chosen strategy by the organization depends not only on the decisions taken in the past but also for the effective implementation of these decisions by the people employed in the organization. That’s why it is important for the company to have clearly defined employee function. Creating the value of the company is rapidly increasing the role of human resources and corporate culture as intangible assets. More specifically, these intangible assets are a decisive factor for the establishment of the value of the company. The management, in general - is the process of rational and effective use of the resources which is achieved through planning, organizing, leading and control. Exactly this issues will be considered in depth and exhaustively, in order to highlight the major benefit of the issue in various capacities. While working on the topic, I used scientific literature, based on the conclusions of the researchers, I tried to get the reasons that prevent the proper use of human resources and to find ways to solve the problems. Internet resources have also been provided, and in case of use it is indicated everywhere. Internet resources have also been used and in case of their use there is everywhere indicated appropriate source. The thesis includes the content, abstract, introduction, the main part of the topic (which is divided into chapters and subchapters), research methodology and analysis, conclusion and the list of used literature.